2015
DOI: 10.3945/jn.115.217299
|View full text |Cite
|
Sign up to set email alerts
|

Young Children's Food Neophobia Characteristics and Sensory Behaviors Are Related to Their Food Intake ,

Abstract: Children's neophobia and sensory sensitivity may be important in understanding underlying issues related to limited food acceptance in typically developing young children and for helping caregivers facilitate healthy dietary intake patterns for their children. This trial was registered at clinicaltrials.gov as NCT01937481.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 44 publications
5
26
1
1
Order By: Relevance
“…Finally, although recent studies have revealed a strong link between child sensory sensitivity and food neophobia (e.g. Coulthard & Blissett, 2009; Johnson et al, 2015), we were unable to include a measure of sensory sensitivity in the present study and our post-hoc analyses did not reveal a link between the temperament dimension of discomfort and food neophobia as might be expected. Thus, it remains unclear how sensory sensitivity may or may not be linked to child temperament.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Finally, although recent studies have revealed a strong link between child sensory sensitivity and food neophobia (e.g. Coulthard & Blissett, 2009; Johnson et al, 2015), we were unable to include a measure of sensory sensitivity in the present study and our post-hoc analyses did not reveal a link between the temperament dimension of discomfort and food neophobia as might be expected. Thus, it remains unclear how sensory sensitivity may or may not be linked to child temperament.…”
Section: Discussioncontrasting
confidence: 51%
“…One example is the dimension of discomfort, defined as negative affect related to sensory qualities of stimulation (Putnam, Rothbart, & Gartstein, 2008). Recent evidence reveals links between food neophobia and taste and smell sensitivity (Coulthard & Blissett, 2009; Johnson, Davies, Boles, Gavin, & Bellows, 2015), as well as a low enjoyment of tactile play measured observationally (Coulthard & Sahota, 2016; Coulthard & Thakker, 2015). Although these studies did not specifically measure child temperament or the dimension of discomfort, sensory sensitivity and discomfort appear to be highly overlapping constructs.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with our hypothesis and previous research that show negative association between food neophobia and vegetable intake (38)(39)(40) .…”
Section: Benefits Of Sensory-based Food Educationsupporting
confidence: 94%
“…Caution should also be exercised when generalizing these results to other populations, especially given the relatively homogenous sample of well-educated, middle-class mothers and the characteristics of the mothers who did not complete the study (less educated, less likely to breastfeed their infants through 6 months of age). Finally, additional variables may be related to infants' responses to novel foods that we were unable to measure in this study, such as parent feeding practices (Lange et al, 2013) or the child's level of sensory sensitivity (Coulthard & Blissett, 2009;Johnson, Davies, Boles, Gavin, & Bellows, 2015).…”
Section: Discussionmentioning
confidence: 99%